STRATEGI PEMELIHARAAN ARSIP DINAMIS INAKTIF MELALUI ALIH MEDIA - Andhika, Daffa Bagus (UPT Perpustakaan Universitas Semarang, 2023)
The Ponorogo Regency Library and Archives Service is a central organization in the field of Libraries and Archives throughout Ponorogo Regency. Along with the development of information technology, the Ponorogo Regency Library and Archives Office has carried out inactive dynamic archive media transfer activities. This study aims to determine the procedure for implementing media transfer in the Ponorogo Regency Library and Archives Office. This research method is a qualitative method with a field study research method through observation and interviews. The results showed that the procedure for transferring inactive dynamic archive media starts from preparing tools for the media transfer process, preparing inactive archives that will be carried out media transfer activities, scanning inactive archives, storing media transfer archives on computer / CD folders as a storage medium for digital inactive archives, returning archives to their original place.